(untitled) (Journal of Fiber Bioengineering and Informatics, 2008)
Textile thermal bioengineering design involves the integration of multidisciplinary knowledge. Utilizing computer power and popularity to realize it creates a huge potential in designing clothing with advanced functions in an effective, economical and scientific way. This paper presents a virtual thermal bioengineering system for life-oriented design of textile products, which, by the combination of multidisciplinary knowledge, creates a virtual space for the designer to achieve textile bioengineering design in a life-oriented way. The thermal bioengineering framework and design principles of thermal functional clothing are shown, the development of the computer-aid system including the life-oriented design, simulation, visualization and project management, as well as the engineering database, is reported with case illustration.